172k views
3 votes
Solve the equation.
- 6y + 8 = - 4(2y + 1)

2 Answers

0 votes

Answer:

y = -6

Step-by-step explanation:

-6y + 8 = -4(2y + 1)

Expand -4(2y + 1): -8y - 4

-6y + 8 = -8y - 4

Subtract 8 From Both Sides

-6y + 8 - 8 = -8y - 4 - 8

Simplify

-6y = -8y - 12

Add 8y To Both Sides

-6y + 8y = -8y - 12 + 8y

Simplify

2y = -12

Divide Both Sides By 2

2y / 2 = -12 / 2

y = -6

User Ashish Thakkar
by
4.8k points
2 votes

Answer:y=2/7

Step-by-step explanation:

User Jeancallisti
by
5.5k points